2015
DOI: 10.14814/phy2.12628
|View full text |Cite
|
Sign up to set email alerts
|

17(R)-resolvin D1 ameliorates bleomycin-induced pulmonary fibrosis in mice

Abstract: Idiopathic pulmonary fibrosis (IPF) is a destructive inflammatory disease with limited therapeutic options. Inflammation plays an integral role in the development of pulmonary fibrosis. Unresolved inflammatory responses can lead to substantial tissue injury, chronic inflammation, and fibrosis. The resolvins are a family of endogenous ω‐3 fatty acid derived‐lipid mediators of inflammation resolution. Resolvin D1 (RvD1) displays potent anti‐inflammatory, pro‐resolving activity, without causing immunosuppression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…Indeed, treatment with resolving D1 decreased inflammatory cell recruitment, production of TGF-, and collagen content in a murine model of BLMinduced lung fibrosis. 29 In the latter experiments, resolving D1 was effective even when given many days after BLM instillation. In contrast, therapeutic administration of Ang- (1-7), which also has clear proresolving activities, 28 failed to decrease BLM-induced lung fibrosis at a dose that worked in a preventive manner.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, treatment with resolving D1 decreased inflammatory cell recruitment, production of TGF-, and collagen content in a murine model of BLMinduced lung fibrosis. 29 In the latter experiments, resolving D1 was effective even when given many days after BLM instillation. In contrast, therapeutic administration of Ang- (1-7), which also has clear proresolving activities, 28 failed to decrease BLM-induced lung fibrosis at a dose that worked in a preventive manner.…”
Section: Discussionmentioning
confidence: 89%
“…At least one other study has shown the effect of another proresolving molecule, resolving D1, in a model of fibrosis in mice. Indeed, treatment with resolving D1 decreased inflammatory cell recruitment, production of TGF‐β, and collagen content in a murine model of BLM‐induced lung fibrosis . In the latter experiments, resolving D1 was effective even when given many days after BLM instillation.…”
Section: Discussionmentioning
confidence: 89%
“…In support of these findings, RvE1 increased collagen in the context of periodontal ligament repair 49 and 17 R -RvD1 was shown to increase matrix synthesis in a model of arthritis 50 . On the other hand, RvD1 was found to decrease cardiac collagen in the setting of myocardial infarction 51 , and there are several reports that suggest SPMs exert anti-fibrotic actions 52 53 . Thus, the role of SPMs in fibrosis appears to be context-specific, and factors that control its actions in collagen synthesis versus degradation in advanced atherosclerosis represents an important area for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RvE1 increases collagen in the periodontal ligament post injury 41 , and 17 R -RvD1 stimulates matrix synthesis in a model of arthritis 42 . Conversely, RvD1 decreases cardiac collagen in the setting of myocardial infarction 43 , and there other reports suggesting that SPMs exert anti-fibrotic actions 44, 45 . Thus, the role of SPMs in collagen synthesis and fibrosis is context-specific, and an understanding of the mechanisms whereby SPMs increase collagen synthesis in advanced atherosclerotic plaques is likely to be a fruitful area of future investigation.…”
Section: 2 Inflammation-resolution and Cardiovascular Diseases (Cvd)mentioning
confidence: 74%